Arah Baru Pendidikan Islam Pasca Uu Pesantren - Suheri, Suheri; Nurrahmawati, Yeni Tri (Proceedings of Annual Conference for Muslim Scholars, 2019)
The concept of Islamic education must be oriented to become a guide in developing the potential of faith in wading through the increasingly complex modernity of life. The existence of Islamic education in Law No. 4 of 1950 which has not been approved by the government so that nothing should be taken for religious studies in schools, then begins with "shy" by the government trying to change the law. 2 years 2989, then the existence of Islamic education began "overtly" by the government in the Act. No. 20 of 2003 both institutions, materials and culture. With the presence of the Pesantren Law, it has become a strong indicator in Islamic Education in Indonesia becoming increasingly entrenched in the education and government system. While the 1945 Constitution mandates the government to implement a national education system that enhances faith and devotion to God Almighty and noble character in order to educate the nation's life. Therefore, Islamic education which is getting stronger and has not been achieved (UU No. 4/1950), has become popular as "shy" (UU No. 2/1989), so that it is increasingly blatant (UU No. 20 / 2003) even exceed completely (UU. Pesantren). The presence of the pesantren law reflects the government's statement of its recognition of the core of Islamic education. However, challenges for pesantren education must be formulated in order to encourage progress in the field of national spiritual and intellectual education